Aplikasi Form Rencana Studi (FRS) Online Di Fakultas Teknik Univesitas Andi Djemma - Ummu Kaltsum Arnis; Apriyanto Apriyanto; Ahmad Ali Hakam Dani (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2018)
Abstract: The application of information technology to universities in principle to facilitate the work process of academic staff, lecturers, and students in terms of accessing data and information. Currently Andi Djemma University Faculty of Engineering still uses conventional methods in managing academic data in the process of filling KRS. This study aims to design an online Study Plan Form application that can facilitate students in filling out KRS online In making this application using qualitative research methods with a type of descriptive research, using Unified Modeling Language (UML) as a system development method and using the PhpMyAdmin database, and designed using a MySQL database with XAMPP software as a web server. The trial results from the application for filling out the Study Plan Form (FRS) online at the Andi Djemma Palopo University Faculty of Engineering show that the KRS filling process is more practical and efficient for students without having to come directly to campus